Isolation of Microbes from Lake Vostok Accretion Ice - D'Elia, Tom (American Society for Microbiology (ASM), 2008)
Bacteria from seven Lake Vostok accretion and two deep glacial Vostok ice core sections were characterized. The cell concentrations were low, but many of the cells were viable. From the hundreds of cultures, 18 unique bacterial rRNA gene phylotypes were determined. Lake Vostok may contain a complex microbial ecosystem.